CHOLEDOCHORRAPHY (PRIMARY REPAIR) VERSUS T-TUBE DRAINAGE AFTER OPEN CHOLEDOCHOTOMY - Saeed, Nadia; Nasir, Muhammad Tauqeer; Khan, Muhammad Iqbal; Channa, Ghulam Asghar (Journal of Ayub Medical College Abbottabad, 2012)
Background: T-tube drainage used to be standard practice after surgical choledochotomy, but there is now a tendency in some canters to close the common bile duct primarily. This study was designed to compare the clinical results of primary closure with T-tube drainage after open choledocotomy and assess the safety of primary closure for future application. Methods: This study was conducted at surgical Unit-3, ward 26 Jinnah Postgraduate Medical Centre Karachi, from January 2007 to January 2008. Forty patients were included in this study out of which 20 underwent primary closure and 20 Ttube placements. It was Quasi-experimental, non-probability, purposive sampling. Main outcome measures were operating time, duration of hospital stay, and postoperative complications. SPSS-10 was used for data analysis. Results: The age of patients in the study ranged from 29-83 years. There were 3 male while 37 female patients. Group-1 consisted of 20 patients underwent primary closure after choledocotomy, while Group-2 also consisted of 20 patients underwent T-tube drainage after duct exploration. Mean hospital stay in Group-1 patients was 7.63 days while in group 2 it was 13.6 days. Overall complication rate in group 1 was 15%, biliary leakage in 1 (5%), jaundice in 1 (5%), wound infection in 1 (5%). No re-exploration was required in Group-1. In Group-2 overall complication rate was 30%, biliary leakage in 2 (2%), jaundice in 1 (5%), dislodgement of T-tube in 1 (5%), wound infection in 1 (5%), and sepsis in 1 (5%) patients. Re-exploration was done in one patient. Conclusion: Primary closure of Common Bile Duct (CBD) is a safe and cost-effective alternative procedure to routine T-tube drainage after open choledocotomy. Keywords: Open choledocotomy, Primary closure, choledocholithiasis